Carcass characteristics and meat quality of broilers fed cassava peel and leaf meals as replacements for maize and soyabean meal (2015)
A 49-day feeding trial involving 180 1-day-old Abhor acre broilers was carried out to evaluate growth and carcass quality of broilers fed cassava leaf meal and cassava peel meals used as replacements of soya bean meal and maize at 20% respectively. Four groups of 45 birds per group of 15 birds per replicate consisting of three replicates per group. Group A served as control (cassava leaf meal (0%) and peelings meal (0%)), Group B (20% cassava peelings -20% leaf meal), C (20% leaf meal -0% cassava peelings) and group D (20% cassava peelings-0% cassava peelings). The cut parts of the carcass showed superior values (p<0.05) in the A (control) treatment and they differed significantly (p<0.05) from broilers on to the group on B (20 % cassava peelings-20 % leaf meal), C (20% leaf meal-0% cassava peelings), D (20% cassava peelings-0% cassava peelings). On the 49th day, the breast muscles of 36 birds were analysed for dry matter, proteins, fat and ash. The organoleptic values were not significantly influenced by the juiciness, taste, colour and overall acceptability among the dietary treatment levels. Up to 20% inclusion of cassava leaf meal and 20% cassava peelings as replacement for soya bean meal and maize respectively in both broiler starter and finisher, diets did not significantly affect growth and carcass yield of broilers.